Amino Acid, Fatty Acid, and Mineral Content of Marine Worm From South East Sulawesi - Nurhikma Nurhikma; Tati Nurhayati; Sri Purwaningsih (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
The coastal communities of Kendari believe that sea worm as traditional drug can cure a wound, because some chemical compounds that exist in sea worms are suspected to have the compound. The aims of this study were to determine chemical compound, amino acid, fatty acid content, and mineral of fleshsea worm (Siphonosoma australe-australe) from Toronipa Aquatic Province Sulawesi Southeast. The higest essential amino acid content on fresh sea worm was arginin (3.04%), and freeze dry was 5.52%. The higest non-essential amino acid content on fresh sea worm and freeze dry were glutamic acid 6.53% and 8.53% for product resulted by freeze dry. The higest saturated attyacid (SF) content of fresh sea worm and freeze dry were palmatic acid (1.96% and 2.64%). The higest MUFA fatty acid content of fresh sea worm and freeze dry were plamitoleat acid 0.31% and 0.27%. The higest poly unsaturated fatty acid (PUFA) of fresh sea worm and freeze dry were were aracidonat 2.80% and oleat acid 1.97%. The higest mineral content of wet sea worm and frezee dry were Natrium 43,700 mg/kg and 127,334 mg/kg.